2018
DOI: 10.1186/s40561-018-0074-x
|View full text |Cite
|
Sign up to set email alerts
|

Using 360-degrees interactive videos in patient trauma treatment education: design, development and evaluation aspects

Abstract: Extremely catastrophic situations are rare in Sweden, which makes training opportunities important to ensure competence among emergency personnel who should be actively involved during such situations. There is a requirement to conceptualize, design, and implement an interactive learning environment that allows the education, training and assessment of these catastrophic situations more often, and in different environments, conditions and places. Therefore, to address these challenges, a prototype system has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…A clear sense of active engagement and participation with the iVR storytelling experience was observed, with most students expressing enthusiasm for the authentic learning experience. Herault et al [44] also concluded that nursing students and faculty agreed immersive VR added value and increased engagement with their education from which the authors concluded that it was a great pedagogical approach to supplement traditional teaching practices. Active student interaction was observed throughout this study with clear signs of positive emotional and facial arousal noted by the research team.…”
Section: Discussionmentioning
confidence: 99%
“…A clear sense of active engagement and participation with the iVR storytelling experience was observed, with most students expressing enthusiasm for the authentic learning experience. Herault et al [44] also concluded that nursing students and faculty agreed immersive VR added value and increased engagement with their education from which the authors concluded that it was a great pedagogical approach to supplement traditional teaching practices. Active student interaction was observed throughout this study with clear signs of positive emotional and facial arousal noted by the research team.…”
Section: Discussionmentioning
confidence: 99%
“…Panoramic videos, also known as Cinematic Virtual Reality (CVR), allow consumers to experience virtual environments via an omnidirectional view by using desktop or mobile applications [15]. Driven by the emergence of affordable head-mounted displays (HMDs), the popularity and consumption of CVR has greatly increased in recent years [44,45] and has encouraged its introduction into entertainment [71], education [29] and vocational training [32,60]. Two key attractions of HMDs are their large Field of View (FOV), which immerses users in virtual environments [18], and their capability to equip users with the freedom to look anywhere by altering their view of the scene using head movements [8,15].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the extent to which cineVR has been used in medical education has been limited, with videos focused primarily in an operating room setting, using real or simulated patients [ 11 , 32 ]. Educational research on the potential of cineVR to augment trauma response training is extremely limited; to our knowledge, only one other study has been published [ 33 ]. In this study, nursing students viewed 360-degree video of trauma teams in Sweden using a desktop computer, and the analysis found that the tool can be a useful addition to existing methods in nursing education.…”
Section: Discussionmentioning
confidence: 99%